PENGARUH KOMPETENSI SUMBERDAYAMANUSIA TERHADAP KINERJA KARYAWAN DI PT. MAYBANK INDONESIA TBK CABANG SILIWANGI KOTA CIREBON - Vina Andita Pratiwi; Elly Herawati; Probo Heryatno (LPPM Sekolah Tinggi Ilmu Ekonomi Cirebon, 2019)
ABSTRACTThis study aims to determine the level of Influence Employee Competency toward Employee Performance PT. Bank Maybank Indonesia Tbk. Where the reponden is a permanent employee of PT. Bank Maybank Indonesia Tbk. with 45 respondents. The distributed questionnaire consisted of 10 questions about employee competence and consisted of 10 questions about employee performance. Base don the results of research conducted, itsshows that thereis a positive effect of employee competency o nemployee performance, PT. Bank Maybank Indonesia Tbk. Siliwangi Branch Cirebon City. It seen from the simple regression equation Y = 4.290 + 0.868X. the analysis that the equation shows a positive influence of the variable X toward variable Y, incresing increase of variable X for 1,it will be influense to increase employee performance at 0.868 poitn . Thus the hypothesis that the researcher submitted accepted, that there is a positive influence of employee competency onemployee performance PT. Bank Maybank Indonesia TbkSiliwangi Branch Cirebon City. So it can be concluded there is partially significant influence of employee competency variables toward employee performance PT. Bank Maybank Indonesia Tbk.AbstrakPenelitian ini bertujuan untuk mengetahui tingkat Pengaruh Kompetensi Sumber DayaManusia Terhadap Kinerja Karyawan Di PT. Maybank Indonesia Tbk. Dimana yangmenjadi reponden adalah karyawan tetap PT. Bank Maybank Indonesia Cabang SiliwangiKota Cirebon dengan 45 responden. Kuesioner yang dibagikan terdiri dari 10 pertanyaanmengenai kompentensi karyawan dan terdiri dari 10 pertanyaan mengenai kinerja karyawan.Berdasarkan hasil penelitian yang dilakukan menunjukan bahwa ada pengaruh positif darikompetensi karyawan terhadap kinerja karyawan PT. Bank Maybank Indonesia CabangSiliwangi Kota Cirebon Dengan demikian hipotesis yang peneliti ajukan diterima, yaitu adasuatu pengaruh positif dari variabel kompetensi karyawan terhadap kinerja karyawan PT.Bank Maybank Indonesia Cabang Siliwangi Kota Cirebon. Sehingga dapat disimpulkan adapengaruh signifikan secaraparsial dari variabel kompetensi karyawan terhadap kinerjakaryawan PT. Bank Maybank Indonesia CabangSiliwangi Kota Cirebon.